Giant cavernous malformations: A single center experience and literature review. (October 2018) - Wang, Chengjun; Zhao, Meng; Wang, Jia; Wang, Shuo; Zhang, Dong; Zhao, Jizong
Highlights: A retrospective study of 9 intracranial giant cavernous malformation patients. The largest case series of GCM from a single neurosurgical center. GCM is more prone to occur in children and adolescents. Epilepsy is the most common initial presentation of GCM. Symptomatic GCMs should be surgically treated. Abstract: Intracranial giant cavernous malformations (GCMs) are rarely reported because of their extremely low incidence. Knowledge of GCM is poor. The goals of this study were to analyze the epidemiological characteristics, clinical manifestations, radiological findings, microsurgical treatment, and neurological outcomes of GCMs. From January of 2003 to December 2016, nine GCM patients who underwent neurosurgical treatment at Beijing Tiantan Hospital were chosen for analysis and their records were reviewed. We also performed an exhaustive literature search and identified all previously reported GCMs. The study population consisted of three males and six females (mean age, 25.1 years). The mean diameter of the malformations was 6.7 cm (range, 6.0–8.4 cm). The most common clinical manifestations were the symptoms caused by mass effect. Radiologically, all GCMs showed mixed T1 and T2 signals; five of them exhibited minimal enhancement after contrast administration. Gross total resection was achieved in all patients without surgical mortality. Postoperatively, three patients developed new surgical complications, including left limbs weakness and left side paralysis. The mean follow-up period after diagnosis was 69.3 months (range, 16–149 months); five patients (55.6%) had achieved full recovery and the remaining four cases (44.4%) were improved to some extent. GCM is a rare subgroup of vascular malformations; it is more prone to occur in children and adolescents. Microsurgical resection should be the treatment of choice for GCMs, and despite their giant size, excellent surgical outcomes after total removal could be achieved.